Discovering 100 birds of Universiti Putra Malaysia - Yahya, Muhammad Syafiq; Puan, Chong Leong; Ishak, Zulkifli (Universiti Putra Malaysia Press, 2017)
Birds are the most widely studied group of vertebrates. They come in various colours, shapes and sizes filling up different levels of a trophic pyramid and occupying many niches of an ecosystem. This includes the top predators such as raptors and small prey species such as sparrows. Birds play significant ecological roles with respect to pollination, seed dispersal, pest control, natural carcass removal, and ecosystem engineering. Collectively, they help maintain the balance of ecosystems. The ability of migratory birds to travel long distances has made them one of the most magnificent taxa in the world. Some species such as hornbills, woodpeckers, owls and waders have been recognized as environmental indicators. In many places, birds have generated significant income locally or nationally through birdwatching tourism. In the Serdang campus of Universiti Putra Malaysia (UPM), a total of 116 bird species of 47 families have been recorded including 23 migrants. The largest family groups are Ardeidae and Sturnidae (each has 9 species), followed by Accipitridae and Pycnonotidae (each has 7 species), and Columbidae (6 species). It is worth to mention that UPM has long been carrying out research on birds ranging from species diversity, species abundance, community assemblages, physiology, systematics, population genetics, ecotoxicology, biological control, behaviour, parasites, diseases to economic values. The Faculty of Forestry, Faculty of Veterinary Medicine, Faculty of Agriculture, Faculty of Science, as well as Faculty of Agriculture and Food Sciences (Bintulu Campus) are among the faculties in UPM that are conducting research on birds.